(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
In the process of building a legal state, guaranteeing the rights and freedoms of citizens and ensuring the effective functioning of the judicial system are of great importance. In this process, the institution of advocacy is considered a crucial mechanism that ensures fair and impartial justice and protects human rights. In Uzbekistan, a deep study of the theoretical and legal foundations of the institution of advocacy and determining its place in the life of society and the state is a necessary condition for the success of reforms in this area. This article provides a comprehensive study of the theoretical and legal foundations, sources, organizational mechanisms, and professional ethics of advocates in the Republic of Uzbekistan.